Legitimacy of Political Power. From Contract Theory to Collective Intentionality - Balayan, Arshak (Bulletin of Yerevan University E: Philosophy, Psychology, 2016)
Attempts to justify the legitimacy of political power through contract theory are discussed in this article. Contract theory is attractive as it seems to enable to justify the legitimacy of political power. However, it has a number of shortcomings. J. Locke’s theory is problematic for its contradictions and unjustified individualism. The theory of tacit consent and I. Kant’s contract theory, on the other hand, threaten the individual freedom. J. Searle replaces the idea of “contract” with that of “collective intentionality”. He claims that it is not that individuals agree to establish a society and government; rather many individuals collectively accept the existence of institutional facts. J. Searle’s central theses are vague. Moreover, many of his claims are incompatible with historical facts.
Keywords: Power, legitimacy, contract, collective intentionality